Rhizomatic Assemblages: Connecting Climate Change to Nursing Action - Vold, Lindsey; Meszaros, Megan (Witness: The Canadian Journal of Critical Nursing Discourse, 2021)
Calls for nursing action to address climate change are resounding throughout the nursing community, yet many nurses feel ill-prepared to engage in climate action. As a collective practice discipline, we argue that nursings’ internalized a rigid view of what nursing is and, through self-disciplining practices, actively police our knowledge and practice to conform within a bounded domain that fails to view global issues, such as climate change, as being within the scope of nursing. To build nurses’ climate action capacity, we draw on Deleuze and Guarttari’s (1987) concept of rhizomatic assemblages to make an explicit connection between health and climate change, but also how climate action is a moral imperative in the scope of nursing education and practice. Using examples in the four domains of nursing - education, practice, research, and policy, we present how nurses can engage in coordinated and collaborative efforts both within and outside of ‘traditional’ nursing practice to address the connecting and complicated pathways of a changing climate.